1979
DOI: 10.1295/polymj.11.323
|View full text |Cite
|
Sign up to set email alerts
|

Alternating Copolymerization of Methyl α-Phenylacrylate and Various Methacrylates

Abstract: Methyl a-phenylacrylate (MPhA) was copolymerized with methacrylates which have ester groups of various sizes, such as benzyl, a-methylbenzyl, diphenylmethyl, a,a-dimethylbenzyl, 1,1-diphenylethyl, and trityl groups. The copolymerization was carried out with butyllithium in toluene and tetrahydrofuran at various temperatures with an initial monomer ratio of 1 : 1. In both solvents the copolymers with highly alternating structure were obtained at O and 30°C, except for the case in which 1,1-diphenylethyl methacr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
11

Year Published

1984
1984
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 10 publications
1
25
0
11
Order By: Relevance
“…18 The utilization of the lithium tertiary alkoxides such as lithium tert-butoxide as initiator and nonpolar solvents gives highly isotactic polymers. 19 The moderate isotacticity of the present sample is reported with the fact that it was possible to examine only the chloroform soluble fraction.…”
Section: Nmr Features Of Anionic Poly(tfema)mentioning
confidence: 99%
“…18 The utilization of the lithium tertiary alkoxides such as lithium tert-butoxide as initiator and nonpolar solvents gives highly isotactic polymers. 19 The moderate isotacticity of the present sample is reported with the fact that it was possible to examine only the chloroform soluble fraction.…”
Section: Nmr Features Of Anionic Poly(tfema)mentioning
confidence: 99%
“…When the formation of high molecular weight product (Mn 2 x 10 4 ) was expected, the polymer was recovered by precipitation from the reaction mixture with hexane, followed by filtration and drying in vacuo. 1 Hand 13C NMR spectra were measured on a JNM-GX500 or JNM-FXIOO NMR spectrometer. In the 1 H NMR spectra of poly(EMA) and copolymer of EMA with MMA measured in CDCI 3 at 55°C and at 100 MHz, the methyl proton signals of ester group in EMA unit overlapped with a-methyl proton signals for the isotactic sequence.…”
Section: Experimentalsmentioning
confidence: 99%
“…In particular, the achievement of stereocontrol during radical polymerization, which is widely used in industry for a variety of monomers, is a significant goal. [1][2][3][4][5] Recently, we found that Lewis acids catalytically affected stereochemistry during the radical polymerization of ␣-(alkoxymethyl)acrylates, 6 -9 methacrylates, 10 and acrylamides; 11 for example, N-isopropylacrylamide afforded a highly isotactic polymer (up to m ϭ 92%) in the presence of yttrium trifluoromethanesulfonate [triflate; Y(OTf) 3 ], whereas a slightly syndiotactic polymer was obtained in the absence of Lewis acids.…”
Section: Introductionmentioning
confidence: 99%